2019
DOI: 10.4236/wjns.2019.94022
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Ligands as Challenge for Positron Emission Tomography of Peptide Receptors in Neurons and Microglia of the Brain

Abstract: Neuropeptide and chemokine receptors of the G protein-coupled receptor (GPCR) family belong to different classes and subgroups providing different docking sites and special binding behavior at extracellular and also transmembrane domains for small molecules potentially suitable for positron emission tomography (PET). The contribution gives an overview updating developments of small-molecule, nonpeptide ligands at a selection of peptide and chemokine receptors, expressed in neurons and microglia of the brain, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…326 Initial PET imaging studies in mice demonstrated the ability to cross the BBB, but further information about in vitro and in vivo validation remains to be reported (Figure 13). 109,327 In addition, a 64 Cu-labeled macromolecule ([ 64 Cu]vMIP-II-comb) was synthesized by conjugating the viral macrophage inflammatory protein-II (vMIP-II) with a 64 Cu-linked nanoparticle. 328 [ 64 Cu]vMIP-IIcomb was specific for chemokine receptors and proved to be useful for an in vivo macrophage mapping in mouse models of peripheral diseases, such as vascular injury and inflammatory atherosclerosis.…”
Section: Pet Probes For Colony Stimulating Factormentioning
confidence: 99%
“…326 Initial PET imaging studies in mice demonstrated the ability to cross the BBB, but further information about in vitro and in vivo validation remains to be reported (Figure 13). 109,327 In addition, a 64 Cu-labeled macromolecule ([ 64 Cu]vMIP-II-comb) was synthesized by conjugating the viral macrophage inflammatory protein-II (vMIP-II) with a 64 Cu-linked nanoparticle. 328 [ 64 Cu]vMIP-IIcomb was specific for chemokine receptors and proved to be useful for an in vivo macrophage mapping in mouse models of peripheral diseases, such as vascular injury and inflammatory atherosclerosis.…”
Section: Pet Probes For Colony Stimulating Factormentioning
confidence: 99%